SSNMR confirms silicate ion substitution in the apatitic structure of 0.8wt% Si hydroxyapatite - Marc-Krystelle Mafina; Rory M. Wilson; Gregory J. Rees; Peter Gierth; Alice C. Sullivan; Karin A. Hing (Academia Materials Science)
This study investigates the structural location of silicon present in ‘silicate-substituted’ apatite. It has been hypothesized that silicon is present in the form of silicate groups site-specifically substituted in the hydroxyapatite lattice for phosphate groups, or that there may be an amorphous silicon-rich phase in the vicinity of the grain boundaries. Solid-state nuclear magnetic resonance (SSNMR) spectroscopy was carried out to view the elemental interactions using phosphorus (31P) and silicon (29Si) probes to confirm or refute the presence of silicate groups in relation to phosphate groups in the bulk material structure. The analysis was performed on stoichiometric hydroxyapatite (HA) and silicate-substituted hydroxyapatite (SA) with a nominal silicon content of 0.8wt%, in as-precipitated, calcined (700°C), and sintered (1,250 and 1,300°C, respectively) powder forms. XRD confirmed all forms of powder were phase pure. FTIR confirmed both hydroxyl and phosphate group functionalities in all forms of HA and SA, while silicate group functionality was only observed in all forms of SA. SSNMR using 31P- and 29Si-coupled probes demonstrated that as the crystallinity of the powders increased from the precipitate to the sintered form, the signal associated with the presence of a silicate group in the phosphate environment developed as the crystal structure became more ordered. These results support the hypothesis that in SA containing 0.8wt% silicon, silicate groups are site-specifically substituted in the hydroxyapatite lattice for phosphate groups. This observation may be key to understanding the mechanisms by which the introduction of 0.8wt% silicon enhances bone regeneration in apatitic bone graft substitute materials.